THE CONCEPT OF MODERNIZATION: AN ANALYSIS OF CONTEMPORARY ISLAMIC THOUGHT (American Journal of Islam and Society, 1997)
One of the main characteristics of contemporary Islamic thought,especially within the traditions of Islamic revival movements and theIslamization of knowledge movement, is its critical attitude toward boththe Islamic heritage and western ideas, concepts, and theories. Thinkersand scholars of these movements have neither rejected entirely the westerncontributions toward knowledge, unlike the rejectionists, nor havethey accepted it blindly, like the adoptationists. Most thinkers in thesemovements do not accept western ideas and concepts without a criticalevaluation from an Islamic perspective. Khurshid Ahmad aptly remarks:The Islamic movement clearly differentiates between developmentand modernization on the one hand and westernization andsecularization on the other. It says “yes” to modernization but“no” to blind westernization.’Such a stance on modernization may not be attributed only to suchIslamic movements as the Muslim Brotherhood of Egypt,2 established byHasan al Banna,’ and the Jama‘at-e-Islami of the Indian subcontinent,~founded by Abul A‘la Mawdudi,’ but also to the Islamization of knowledgemovement.6 The type of modernization welcomed by scholars ofthese movements is not the same as that conceived by the West; rather,it is an Islamic modernization based on an Islamic epistemology ...